2006
DOI: 10.1111/j.1461-0248.2006.00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal frequency affects local biomass production by controlling local diversity

Abstract: Dispersal is a major factor regulating the number of coexisting species, but the relationship between species diversity and ecosystem processes has mainly been analysed for communities closed to dispersal. We experimentally investigated how initial local diversity and dispersal frequency affect local diversity and biomass production in open benthic microalgal metacommunities. Final local species richness and local biomass production were strongly influenced by dispersal frequency but not by initial local diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
94
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 50 publications
6
94
0
3
Order By: Relevance
“…This was achieved for light (except for ultraviolet radiation that was excluded by the roof), water temperature, salinity and nutrient concentrations. By using unfiltered seawater and letting water exit through an overflow, the sediment remained an open system (Matthiessen & Hillebrand 2006), allowing immigration and emigration of larvae and spores. By using undisturbed sediment, the natural organism diversity, as well as heterogeneity (patchiness) could be retained.…”
Section: Methodsmentioning
confidence: 99%
“…This was achieved for light (except for ultraviolet radiation that was excluded by the roof), water temperature, salinity and nutrient concentrations. By using unfiltered seawater and letting water exit through an overflow, the sediment remained an open system (Matthiessen & Hillebrand 2006), allowing immigration and emigration of larvae and spores. By using undisturbed sediment, the natural organism diversity, as well as heterogeneity (patchiness) could be retained.…”
Section: Methodsmentioning
confidence: 99%
“…But, we argue that if the only source of niche differentiation is regional (as in the source sink models), then the scale of the positive BEF should be regional. The scarce experiments conducted in source-sink systems have revealed a positive effect of diversity on productivity at both local (Matthiessen & Hillebrand 2006) and regional scales (Venail et al 2008). We are unaware of any experimental study simultaneously addressing the BEF relationship at both local and regional scales.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the microcosm communities cover substantial biological complexity in terms of more structured trophic levels and species interactions that cannot be entirely captured by any model (24) (Materials and Methods and SI Materials and Methods). Previous microbial experiments found that spatiotemporal heterogeneity among local communities induced by disturbance (25) and dispersal (26)(27)(28) events has a strong influence on species coexistence and biodiversity. In previous works (20,22,26,28) the focus was mostly on dispersal distance, dispersal rates, and dispersal kernels and how they affect diversity patterns in relatively simple landscapes.…”
mentioning
confidence: 99%
“…Previous microbial experiments found that spatiotemporal heterogeneity among local communities induced by disturbance (25) and dispersal (26-28) events has a strong influence on species coexistence and biodiversity. In previous works (20,22,26,28) the focus was mostly on dispersal distance, dispersal rates, and dispersal kernels and how they affect diversity patterns in relatively simple landscapes. These factors, directly affecting the history of community assembly (29, 30), introduce variability in community composition in terms of abundances and local species richness.…”
mentioning
confidence: 99%